C8 THE CEREBRAL PERFORMANCE CATEGORY IN THE DECISION–MAKING PROCESS OF IMPLANTING AN ICD IN OUT–OF–HOSPITAL CARDIAC ARREST SURVIVORS WITH BAD NEUROLOGICAL OUTCOME. (18th May 2022) - Compagnoni, S; Baldi, E; Primi, R; Gentile, F; Bendotti, S; Currao, A; Bertona, R; Buratti, S; Raimondi Cominesi, I; Taravelli, E; Fava, C; Moschini, L; et al.
Abstract: Introduction: According to the European Society of Cardiology guidelines secondary prevention ICD implantation is a class I indication only for those patients with an estimated survival > 1 year with a good functional status. However, it is not specified how to assess the functional status and its evaluation could be quite difficult in the case of out–of–hospital cardiac arrest (OHCA) survivors with major neurological outcomes. Cerebral Performance Category (CPC) is the most widespread scale to define the neurological and functional outcome of OHCA survivors, but it is not known if it can be used to guide ICD implantation. Objective: To evaluate whether the presence of a bad neurological outcome (CPC > 2) at discharged could be used as a prognostic index in order to evaluate the implantation of an ICD in OHCA survivors. Materials and Methods. We considered all the patients who had a cardiac arrest from 01/10/2014 to 30/09/2019 presenting a CPC> 2 at discharge. The territory included was that of the Province of Pavia (550000 inhabitants) from 2014 to 2018 and of the Provinces of Pavia, Lodi, Cremona and Mantua (1550000 inhabitants) from 2019. We assessed the survival and the neurological status variation at 1–year. Results: In the study period, CPR was attempted in 2998 confirmed OHCAs. 227 patients (7.6%) were discharged alive and in 218 of these, CPC was available. 51 patients (23.4%) had a CPC>2 at discharge (22 CPC = 3, 24 CPC = 4 and 5 CPC = A). 1–year follow–up was available in 200 patients: among 158 alive, 12 (7.6%) had CPC>2 (7 CPC = 3 and 5 CPC = 4). 1–year survival of patients with CPC>2 at discharge was significantly lower those discharged with CPC≤2 (39.6% vs 91.6% p < 0.001). Only 19/48 patients discharged with CPC>2 survived at 1 year: a good cerebral performance was recovered in 6 patients (31.6%), while CPC>2 persisted in 11 (58%) and the CPC value was unknown in 2 of them. Conclusions: Our results highlight that 1–year survival is quite low in patients with CPC>2 at discharge and that an improvement in cerebral performance occurs only in a minority of them. This evidence suggests the need for clinical re–evaluation after the event in order to carefully evaluate whether to implant an ICD in this kind of patients.